2005
DOI: 10.1128/jcm.43.8.4041-4045.2005
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Differentiation and Comparison of Desulfovibrio Species and Other Phenotypically Similar Genera

Abstract: Seventeen human clinical isolates representing four species of Desulfovibrio were characterized using 16S rRNA gene sequences and tests for catalase, indole, nitrate, bile, urease, formate-fumarate stimulation, desulfoviridin, motility, and hydrogen sulfide production, plus susceptibility to antimicrobial agents. Eighty additional strains representing 10 phenotypically similar genera (Bilophila, Selenomonas, Capnocytophaga, Campylobacter, Bacteroides, Sutterella, Anaerobiospirillum, Dialister, Veillonella, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 30 publications
2
83
0
1
Order By: Relevance
“…In terms of the diversity of the SRB found, there appeared to be a slight edge for the lignocellulose-based BCRs, in which 3-4 different kinds of SRB were identified, whereas 2-3 different kinds were identified in the ETOH BCRs. These SRB may vary from one another in terms of substrate utilization capabilities, kinetics and other characteristics such as tolerance to oxygen exposure and other stresses (Warren et al, 2005). This could have a significant impact on BCR performance.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the diversity of the SRB found, there appeared to be a slight edge for the lignocellulose-based BCRs, in which 3-4 different kinds of SRB were identified, whereas 2-3 different kinds were identified in the ETOH BCRs. These SRB may vary from one another in terms of substrate utilization capabilities, kinetics and other characteristics such as tolerance to oxygen exposure and other stresses (Warren et al, 2005). This could have a significant impact on BCR performance.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical testing. Biochemical tests performed at the R. M. Alden Research Laboratory included determination of susceptibility to special potency disks of kanamycin (1,000 g), vancomycin (5 g), and colistin (10 g) as well as catalase, spot indole, nitrate reduction, growth on bile, urease, growth stimulation with formate/fumarate, and SIM (sulfide-indole-motility), as described previously (22). In addition, an enzymatic profile was determined using the RapID ANA II system (Remel, Lenexa, KS) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Culture-independent studies have demonstrated their presence in man during endodontic or periodontic infections, in dental caries (Munson et al, 2002(Munson et al, , 2004Siqueira & Rôças, 2005, 2007Hutter et al, 2003), in subgingival plaque (Paster et al, 2001), in faeces (Horz et al, 2006) and in vaginal flora (A. Damay, H. Marchandin, L. Roudière, C. Teyssier, H. Dechaud, H. Jean-Pierre, E. Jumas-Bilak, unpublished results). However, only eight human isolates have been reported to date (Munson et al, 2002;Warren et al, 2005;Horz et al, 2006).…”
mentioning
confidence: 99%
“…Strain RMA 10849 was obtained from the collection of the R. M. Alden Research Laboratory, Santa Monica, CA, USA. This isolate originated from a sacral wound and was previously described as an unnamed organism by Warren et al (2005) and further described as belonging to 'Synergistes' group organisms by Horz et al (2006). Colony morphology and the responses of the strains to special potency disks (Jousimies-Somer et al, 2002) were observed on Columbia sheep blood agar plates.…”
mentioning
confidence: 99%
See 1 more Smart Citation